Predicting Mortality in Gastric Perforation: A Comparative Analysis of Boey Score and Mannheim Peritonitis Index Accuracy in an Indonesian Tertiary Hospital - Bobi Wijaya; Alsen Arlan; Theodorus (Sriwijaya Journal of Surgery, 2025)
Introduction: Peptic ulcer perforation (PUP), often leading to gastric perforation, represents a significant surgical emergency demanding rapid intervention. Effective risk stratification using prognostic scoring systems is crucial for optimizing patient management and improving outcomes. This study aimed to evaluate and compare the predictive performance of the Mannheim Peritonitis Index (MPI) and the Boey Score in estimating in-hospital mortality risk among patients presenting with gastric perforation at a tertiary hospital in Indonesia. Methods: A retrospective descriptive study employing an accuracy testing design was conducted. Data were collected from the medical records of 31 adult patients (≥18 years) who underwent exploratory laparotomy for non-traumatic gastric perforation at Dr. Mohammad Hoesin General Hospital Palembang, between January 2023 and December 2024. Patients with incomplete medical records were excluded. Boey Scores and MPI scores were calculated for each patient based on predefined criteria. The primary outcome measured was in-hospital mortality. Statistical analysis included descriptive statistics, calculation of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, and Receiver Operating Characteristic (ROC)1 curve analysis to determine optimal cutoff values. Results: The median age was 62 years, with a male predominance (87.1%). Most patients presented late (>24 hours post-perforation, 90.3%) and had organ dysfunction (80.6%). Preoperative shock was present in 48.4%. The optimal cutoff for MPI predicting mortality was ≥22, yielding a sensitivity of 87.5% and specificity of 40.0%. The optimal Boey Score cutoff was ≥2, with a sensitivity of 75.0% and specificity of 53.3%. Comparing MPI (cutoff ≥22) against Boey Score (cutoff ≥2) as a reference, the MPI demonstrated an accuracy of 74.19%, sensitivity of 73.91%, specificity of 75.00%, PPV of 89.47%, and NPV of 50.00%. Conclusion: Both the Boey Score and MPI showed moderate predictive performance for in-hospital mortality in patients with gastric perforation in this cohort. MPI (cutoff ≥22) demonstrated higher sensitivity for identifying high-risk patients compared to the Boey Score (cutoff ≥2), although with lower specificity regarding mortality itself. MPI appears advantageous for identifying high-risk individuals, while the simpler Boey Score remains useful for rapid initial assessment.